Sistem Pedukung Keputusan Pemilihan Lokasi Pemasangan Wifi.Id Pada PT. Telkom Indonesia ( Witel Bekasi ) - Putri Nabila Vitria; Nadya Safitri (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2021)
Abstract: Wifi.id is a broadband access network that is a medium for enjoying high-speed internet services up to 100 Mbps and various other multimedia services. Wifi.id is a place where we can access the internet with a good network that was built to meet the needs of the community to surf at high speed and pay at an affordable price. This Wifi.id service can only be found in a few places because this Wifi.id service is only installed in places where the location meets the standards. The purpose of this study is to find out locations that meet the right standards for installing wifi.id services because in placing wifi.id installation locations the right considerations and decisions are needed. In this study, researchers used several criteria, namely Fiber Optic, Spec Distance, Fiber Optic Attenuation, and location density. The method used in this study is the SAW method which can make decisions to find out the appropriate location for installing Wifi.id services in an effective way for complex problems. Keywords: Distance, Fiber Optic, Internet, Location, SAW, Wifi.id